The extent and limits of the judged thing “secundum eventum probationis” in the framework of popular action and public civil action (Research, Society and Development, 2022)
One of the foundations of the Democratic State of Law is the stability inherent in the definitive pronouncements derived from the Judiciary, commonly represented by the legal-procedural institute of the judged thing, which also sometimes makes the mechanism responsible for maintaining legal certainty in procedural relations governed by the legislation in force. In this sense, based on a qualitative research, carried out through a bibliographic review, especially based on jurisprudential analysis, this article will briefly address the formation of the thing judged "secundum eventum probationis" in the context of popular action and public civil action, recalling, to that end, the authorized doctrinal teaching of national jurists and the dominant jurisprudence of the Superior Court of Justice,  thus, aiming to contribute to the dissemination of legal knowledge about the formation and incidence of this negative assumption in these collective actions, recognizing, however, the non-exhaustion of the theme addressed here, given the dynamic ity of legal knowledge, particularly in its procedural aspect, which directly affects the resolution of social conflicts.